Science and Dissemination for the UN Ocean Decade Outcomes: Current Trends and Future Perspectives - Francesco Caruso; Pietro Tedesco; Gerardo Della Sala; Fortunato Palma Esposito; Marco Signore; Simonepietro Canese; Teresa Romeo; Marco Borra; Claudia Gili; Donatella de Pascale (Frontiers in Marine Science, 2022)
The Ocean Decade (OD) is the name of a United Nations (UN) initiative devoted to ocean science for sustainable development. It started in 2021 and will provide an opportunity to create a new foundation, across the science-policy interface, to strengthen the sustainable management of oceans and coasts and, at same time, bring benefits for future generations. The OD will establish a common strategy to achieve the objectives of the 2030 Agenda for Sustainable Development and the other European Union (EU) and international agreements, such as the EU Marine Strategy Framework Directive (MSFD), the Marine Biodiversity Strategy and the UN World Assessment I and II aimed at preserving ocean health. Furthermore, the OD has several expected outcomes that concern different aspects of marine environment, including its enormous values for humans. Several entities will combine efforts to achieve these goals and science is at the forefront of the sustainable blue economy. Marine research is solving complex challenges through interdisciplinary approaches, revolutionizing our life and our interaction with the ocean. This review discusses recent advancements in science related to the OD outcomes. The role of new technology for ocean exploration and monitoring, the importance of omics science and biotechnology to deal with ocean pollution, and other innovative solutions are discussed. All of these are inspired by the idea of using marine resources in a sustainable way and without impacting in a negative way on marine ecosystems. The role of science communication is therefore considered a crucial issue to spread the OD messages and to reach the general public and stakeholders. Only by the integration of science, governance, industry and public, the OD will have any chance to succeed.

Vertebrate-rich Plattenkalk of Pietraroia (Lower Cretaceous, Southern Apennines, Italy): a new model - Gabriele Carannante; Marco Signore; Mario Vigorito (Facies, 2006)